Implementasi Lean Manufacturing dan Menghindari Tabdzir untuk Peningkatan Produktifitas dengan Minimasi Waste - Afrianty, Nonie (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2021)
This study aims to determine the causes of waste and minimize the causes of waste in the production process by using a lean manufacturing approach and analyzing it from an Islamic economic perspective. This type of research is field research with a qualitative approach. The informants of this study were the owner and 9 employees of the Saf'fana Furniture Store. The analysis technique used uses several tools, including VSM, Fishbone diagrams, Failure Mode and Effect Analysis. The results of this study indicate that the cause of the emergence of waste in the production process lies in the time of the drying process and repair of defective goods, the way to minimize it is to increase the stock of raw materials and increase worker discipline so that product defects do not occur, while in the perspective of Islamic economics the production process is classified as on tabzir because the time used to dry the raw materials and after the finished product must be repaired again on the defective goods, thus need creativity and discipline to workers